2022
DOI: 10.1021/acsomega.2c00460
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Biodegradation of Crude Petroleum Oil in Water by Photostimulated Janibacter terrae Strain S1N1

Abstract: Biodegradation is a sustainable green strategy that gives the opportunity for remediation of water contaminated with petroleum products. In this study, 12 bacterial isolates were recovered from River Nile, Egypt and screened for their potential to degrade a mixture of paraffinic petroleum crude oil. The most promising isolate was identified according to 16S rRNA sequencing as Janibacter terrae strain S1N1 (GenBank accession No. KX570955.1). In order to boost the biodegradation efficiency… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Trying to improve the performance of MFCs, the bacterial consortium was subjected to LLRL to enhance the cell proliferation, protein synthesis and metabolic activities [20]. Previous studies on the effect of laser radiation indicates its bio-stimulatory effect, this effect returned to the photoexcitation of the protein cytochrome C complex, consequently it pumps more photons thus the amount of ATP increases leading to increase in the growth rate, on the other hand high irradiation doses causes cytotoxic effect leading to the damage of the cell structure [28], our results are harmonious with those of Crugeira et al [18] who reported that the stimulatory effect of LLRL is dose dependent and has positive influence on thermophilic bacterial kinetics. In an application of assessing the efficiency of new MFC designed using sludge which contain the metabolically active bacterial cells as culture medium was done, addition of exogenous bacterial inoculum of the photo-stimulated bacterial consortium led to significantly high synergistic action that increased the cell performance, as acceleration of cell proliferation consequently led to intensifying the electron flow, also the addition of fresh medium containing glucose /pyruvate (1%) at regular intervals over comes the depletion of nutrients and led to the revival of the endogenous and exogenous microbial flora, thus the mean value of the potential difference was maintained during the time of operation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Trying to improve the performance of MFCs, the bacterial consortium was subjected to LLRL to enhance the cell proliferation, protein synthesis and metabolic activities [20]. Previous studies on the effect of laser radiation indicates its bio-stimulatory effect, this effect returned to the photoexcitation of the protein cytochrome C complex, consequently it pumps more photons thus the amount of ATP increases leading to increase in the growth rate, on the other hand high irradiation doses causes cytotoxic effect leading to the damage of the cell structure [28], our results are harmonious with those of Crugeira et al [18] who reported that the stimulatory effect of LLRL is dose dependent and has positive influence on thermophilic bacterial kinetics. In an application of assessing the efficiency of new MFC designed using sludge which contain the metabolically active bacterial cells as culture medium was done, addition of exogenous bacterial inoculum of the photo-stimulated bacterial consortium led to significantly high synergistic action that increased the cell performance, as acceleration of cell proliferation consequently led to intensifying the electron flow, also the addition of fresh medium containing glucose /pyruvate (1%) at regular intervals over comes the depletion of nutrients and led to the revival of the endogenous and exogenous microbial flora, thus the mean value of the potential difference was maintained during the time of operation.…”
Section: Discussionmentioning
confidence: 99%
“…Photo stimulation of the selected electrogenic bacterial consortium was carried out in the National Research Centre (NRC), Egypt using low level red laser (LLRL) tube (ThORLABS, USA) at wave length of 632.8 nm and output power 8 mW, an adjustable stand was used to stabilize the laser tube at 20mm height, irradiation takes place in dark room at 30 ± 2ºC, the bacterial suspension of the bacterial consortium at optimum conditions was subjected to different radiation doses via different exposure intervals (0, 30, 60, 90, 120, 150, 180, 210, 240 sec), the standard bacterial suspensions were inoculated in triplicate screw capped 250mL bottles containing 100mL BM medium, after 24h of incubation at 30ºC the TVC was recorded as cfu/mL as in the optimization step [28].…”
Section: Photo Stimulation Of Electrogenic Bacterial Consortiummentioning
confidence: 99%
“…Because of different polarity natures, the separation of immiscible oil from water solutions is relatively simple. However, it is difficult to break apart oil/water emulsions due to their small particle size (almost smaller than 20 μm), which are stabilized by surfactants. , The conventional approaches for the treatment of oil-contaminated wastewater include chemical (e.g., electrocoagulation and demulsification), , biological (e.g., biodegradation), and physical methods (e.g., skimming, air flotation, and centrifugation). ,- As a drawback, these methods often have low efficiency, particularly for separating emulsified oil–water mixtures . They also suffer from complex operational processes, high energy costs, and the risk of secondary contamination.…”
Section: Introductionmentioning
confidence: 99%